THE EFFECT OF HELPING EMPLOYEES LEARN NEW SKILLS ON THE GROWTH AND PERFORMANCE OF ORGANIZATIONS - Rani, Mamta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
It looks into how assisting employees in learning new skills influences the expansion and work of organizations. Because the business world is changing so fast and can be very competitive, successful companies depend on employees who are highly skilled and flexible. This is most effectively done by using ongoing learning and training programs at the workplace. The study aims to explain how boosting employee skills makes companies work better, see rise in productivity, achieve higher levels of employee satisfaction, improve innovation and contribute to the organizations overall expansion. Information was gathered from people working in various organizations by using surveys and interviews. Most employees said they feel more motivated and dedicated when they are given the opportunity to enhance their skills. Businesses that focus on such programs notice better results, more success and fewer workers leaving. This study shows that when employees grow, both teams and the organization perform well. If organizations build a culture where learning happens, they grow stronger, come up with better ideas and are prepared for upcoming changes. The research points to training as an essential step for keeping a business successful over time.